Congenital diaphragmatic hernia presenting with symptoms within the first day of life; outcomes from a non-ECMO centre in Denmark - Ulla Lei Larsen; Søren Jepsen; Thomas Strøm; Niels Qvist; Palle Toft (BMC, 2020)
Abstract Background Between 1998 and 2015, we report on the survival of congenital diaphragmatic hernia (CDH)-infants presenting with symptoms within the first 24 h of life, treated at Odense University Hospital (OUH), a tertiary referral non-extracorporeal membrane oxygenation (ECMO) hospital for paediatric surgery. Methods We performed a retrospective cohort study of prospectively identified CDH-infants at our centre. Data from medical records and critical information systems were obtained. Baseline data included mode of delivery and infant condition. Outcome data included 24-h, 28-day, and 1 year mortality rates and management data included intensive care treatment, length of stay in the intensive care unit, time of discharge from hospital, and surgical intervention. Descriptive analyses were performed for all variables. Survivors and non-survivors were compared for baseline and treatment data. Results Ninety-five infants were identified (44% female). Of these, 77% were left-sided hernias, 52% were diagnosed prenatally, and 6.4% had concurrent malformations. The 28-day mortality rate was 21.1%, and the 1 year mortality rate was 22.1%. Of the 21 non-survivors, nine died within the first 24 h, and 10 were sufficiently stabilised to undergo surgery. A statistically significant difference was observed between survivors and non-survivors regarding APGAR score at 1 and 5 min., prenatal diagnosis, body length at birth, and delivery at OUH. Conclusions Our outcome results were comparable to published data from other centres, including centres using ECMO.